Shipboard measurements of the hearing of the white-beaked dolphin Lagenorhynchus albirostris - Nachtigall, P. E.; Mooney, T. A.; Taylor, K. A.; Miller, L. A.; Rasmussen, M. H.; Akamatsu, T.; Teilmann, J.; Linnenschmidt, M.; Vikingsson, G. A. (Journal of Experimental Biology, 2008)
This is the first report of an underwater audiogram from a dolphin in a capture-and-release scenario. Two bow-riding white-beaked dolphins Lagenorhynchus albirostris (a female and a male) were captured using the hoop-net technique in Faxaflói Bay, Iceland. The dolphins were transferred to a stretcher and hoisted into a plastic research tank on board a small fishing vessel. Two underwater transducers were used to cover the frequency range from 16 to 215 kHz. Two human EEG electrodes mounted in suction cups, one placed near the blow hole and the other on the dorsal fin, picked up bioelectrical responses to acoustic stimuli. Responses to about 1000 sinusoidal amplitude modulated stimuli for each amplitude/frequency combination were averaged and analyzed using a fast Fourier transform to obtain an evoked auditory response. Threshold was defined as the zero crossing of the response using linear regression. Two threshold frequencies at 50 kHz and 64 kHz were obtained from the female. An audiogram ranging from 16 to 181 kHz was obtained from an adult male and showed the typical `U' shaped curve for odontocetes. The thresholds for both white-beaks were comparable and demonstrated the most sensitive high frequency hearing of any known dolphin and were as sensitive as the harbor porpoise.